-24+3n=-4(-3-3n)

Simple and best practice solution for -24+3n=-4(-3-3n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -24+3n=-4(-3-3n) equation:


Simplifying
-24 + 3n = -4(-3 + -3n)
-24 + 3n = (-3 * -4 + -3n * -4)
-24 + 3n = (12 + 12n)

Solving
-24 + 3n = 12 + 12n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-12n' to each side of the equation.
-24 + 3n + -12n = 12 + 12n + -12n

Combine like terms: 3n + -12n = -9n
-24 + -9n = 12 + 12n + -12n

Combine like terms: 12n + -12n = 0
-24 + -9n = 12 + 0
-24 + -9n = 12

Add '24' to each side of the equation.
-24 + 24 + -9n = 12 + 24

Combine like terms: -24 + 24 = 0
0 + -9n = 12 + 24
-9n = 12 + 24

Combine like terms: 12 + 24 = 36
-9n = 36

Divide each side by '-9'.
n = -4

Simplifying
n = -4

See similar equations:

| 3c^2=243 | | 77+76+81+78+2x/6=80 | | (X-6/5)=(2/3) | | .20x+.45(50)=26.5 | | -11-8n=5n-2n | | 2c^2-17/8c-8 | | 5c^2=324 | | 8(x-5)+2=3x-3 | | f(x)=(x+2)-16 | | 6(7+6n)=5-n | | 2x=10x-90 | | -(3y+3z-8)= | | 4(5x-2)+6=38 | | Cot(cos^-1(7x/8)) | | -3x^2+56x+29=0 | | 2x=5x-90 | | 15x+4=-2x+21 | | 3k^4+10k^3-48k^2=0 | | -3x^2+56t+29=0 | | (3w)w=300 | | 1/18=9.5/x | | 9-(2x-1)=45 | | 8x+4=4x+(-4) | | -5x+3.2=-3.2x+3.6 | | W/2=71 | | f(x)=(x+4)-25 | | 4x/9-7=1 | | .75(h+6)=15 | | 4x-2X+x+59= | | 12(z+2)-4(z-4)=3(z-1)+4(z-3) | | 10-d=-34+5d | | 5(n+8)=n+28 |

Equations solver categories